Preventive and Therapeutic Effects of a Novel JAK Inhibitor SHR0302 in Acute Graft-Versus-Host Disease. (15th July 2021) - Sun, Xi; He, Qiaomei; Yang, Jun; Wang, Andi; Zhang, Fang; Qiu, Huiying; Zhou, Kun; Wang, Pengran; Ding, Xiaodan; Yuan, Xiujie; Li, Huajun; Zhang, Yan; et al.
Acute graft-versus-host disease (aGVHD) is one of the most common complications of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Janus kinase (JAK) inhibitors are considered as reliable and promising agents for patients with aGVHD. The prophylactic and therapeutic effects of SHR0302, a novel JAK inhibitor, were evaluated in aGVHD mouse models. The overall survival (OS), progression-free survival (PFS), bodyweight of mice, GVHD scores were observed and recorded. The bone marrow and spleen samples of diseased model mice or peripheral blood of patients were analyzed. SHR0302 could prevent and reverse aGVHD in mouse models with preserving graft-versus-tumor effect. Functionally, SHR0302 improved the OS and PFS, restored bodyweight, reduced GVHD scores, and reduced immune cells infiltrated in target tissues. SHR0302 treatment also enhanced the hematopoietic reconstruction compared to the control group. Mechanistically, our results suggested that SHR0302 could inhibit the activation of T cells and modulate the differentiation of helper T (Th) cells by reducing Th1 and increasing regulatory T (Treg) cells. In addition, SHR0302 decreased the expression of chemokine receptor CXCR3 on donor T cells and the secretion of cytokines or chemokines including interleukin (IL)-6, interferon γ (IFN-γ), tumor necrosis factor α (TNF-α), CXCL10, etc. thereby destroying the IFN-γ/CXCR3/CXCL10 axis which promotes the progression of GVHD. Besides, SHR0302 decreased the phosphorylation of JAK and its downstream STATs, AKT and ERK1/2, which ultimately regulated the activation, proliferation, and differentiation of lymphocytes. Experiments on primary cells from aGVHD patients also confirmed the results. In summary, our results indicated that JAK inhibitor SHR0302 might be used as a novel agent for patients with aGVHD.